Tinjauan biomimikri pada bentuk umpan pancing ikan artifisial - Bernando, Ardo (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2024)
This research examines the form relations of artificial fishing lure designs created from the inspiration of living creatures. The study was conducted to identify the various forms of artificial fishing lures and the types of living things they imitate, by collecting data on artificial fishing lures through direct observation, internet studies, and literature studies. The research method used was qualitative with a collective or compound case study approach. It was found that not all artificial fishing lures are realistically similar to living creatures, even in the category of metal wire baits, the shapes tend to be abstract and difficult to guess, but can still be used for fishing. It was also found that some of these baits when used have simulated movements like living things because there are various features that support their bodies such as weights, pendulums, rotating blades and so on. The results of this research can be used as recommendations for developing aspects of design forms based on the Biomimicry method in making decisions to solve problems in the scientific field of product design.